IMPLEMENTASI PELAYANAN KIA MELALUI WEBSITE KLAMPID NEW GENERATION DI KELURAHAN MEDOKAN AYU KOTA SURABAYA - Tesalonika Devvany Nugroho; Oktarizka Reviandani (Halu Oleo University, 2024)
Identity is a constitutional right for all Indonesian citizens. The issuance of citizens who aren’t in 17 years old is carried out by Dinas Kependudukan dan Pencatatan Sipil by supporting the publication of Kartu Identitas Anak as for the citizens who haven’t in age 17 years old to get their KTP-El. This regulation is supported by Peraturan Daerah Kota Surabaya Nomor 6 Tahun 2019 Pasal 1 Ayat 20 about Kartu Identitas Anak the official identity for children under 17 years old. This research uses descriptive qualitative research methods. The results of this research are the application of the Klampid New Generation website in issuing Kartu Identitas Anak in Kelurahan Medokan Ayu which is presentable but still requires improvements in aspects through telecommunications, services and human resources.